Estimation of Mangrove Canopy Cover in The Carocok Tarusan Tourist Area - Irawan, Fiska Asif; Mukhtar, Erizal; Solfiyeni, Solfiyeni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The mangrove canopy cover is the uppermost layer in the mangrove vegetation group, which is formed by the crown (leaf group) of mangrove vegetation and covers the layer below. The purpose of the study is to determine the estimation of mangrove canopy cover in the Carocok area using the MonMang v2.0 application and to determine the influence of environmental factors on the mangrove canopy cover in the Carocok area. This research was conducted from December 2023 to January 2024 in the Carocok Tarusan tourist area, Pesisir Selatan Regency, West Sumatra.The method used in this study is the transect line method with the placement of transects carried out from the coastline to the land that has true mangrove vegetation. In the transect line, 20 plots were mapped with a size of 5 x 5 m. Then, the crown cover was measured using the MonMang v2.0 application using the hemispherical photography method on each plot. The results of the study show that the average mangrove canopy cover in this Carocok area is 69.19% and is classified as a medium category. The results of the study also showed that environmental factors between salinity, temperature, and pH had an influence on the mangrove canopy cover in the Carocok Tarusan area.